Preliminary study of a new gamma imager for on-line proton range monitoring during proton radiotherapy. (23rd May 2017) - Bennati, P.; Dasu, A.; Colarieti-Tosti, M.; Lönn, G.; Larsson, D.; Fabbri, A.; Galasso, M.; Cinti, M.N.; Pellegrini, R.; Pani, R.
Abstract: We designed and tested new concept imaging devices, based on a thin scintillating crystal, aimed at the online monitoring of the range of protons in tissue during proton radiotherapy. The proposed crystal can guarantee better spatial resolution and lower sensitivity with respect to a thicker one, at the cost of a coarser energy resolution. Two different samples of thin crystals were coupled to a position sensitive photo multiplier tube read out by 64 independent channels electronics. The detector was equipped with a knife-edge Lead collimator that defined a reasonable field of view of about 10 cm in the target. Geant4 Monte Carlo simulations were used to optimize the design of the experimental setup and assess the accuracy of the results. Experimental measurements were carried out at the Skandion Clinic, the recently opened proton beam facility in Uppsala, Sweden. PMMA and water phantoms studies were performed with a first prototype based on a round 6.0 mm thick Cry019 crystal and with a second detector based on a thinner 5 × 5 cm 2, 2.0 mm thick LFS crystal. Phantoms were irradiated with mono-energetic proton beams whose energy was in the range between 110 and 160 MeV. According with the simulations and the experimental data, the detector based on LFS crystal seems able to identify the peak of prompt-gamma radiation and its results are in fair agreement with the expected shift of the proton range as a function of energy. The count rate remains one of the most critical limitations of our system, which was able to cope with only about 20% of the clinical dose rate. Nevertheless, we are confident that our study might provide the basis for developing a new full-functional system.